Determinan Sikap Remaja terhadap Pernikahan Dini di Provinsi Banten: Analisis Data SKAP 2019 - Evi Avicenna Agustin; Sri Susanti; Rd. Deden Gumilar (Faletehan Health Journal, 2021)
The marriage law states that the ideal marriage for men is over the age of 21 and women over the age of 19. The social problem of early marriage in Indonesia is a phenomenon that occurs in many areas, both in urban and rural areas, such as the high rate of divorce and maternal and infant mortality. The purpose of this study was to determine the factors that influence adolescent attitudes towards early marriage in Banten Province based on the 2019 Program Performance and Accountability Survey. The research design was cross-sectional with the total sample of 1,458. The results showed that there was a relationship between age (p=0.001; OR=16.7; 95%CI=12.5-22.4), sex (p=0.001; OR=2.51; 95%CI=2, 01-3.12), education (p=0.001; OR=0.09; 95%CI=0.06-0.12), knowledge (p=0.001; OR=4.11; 95%CI=3.26 -5.17) and adolescent attitudes towards early marriage. Meanwhile, residence did not have a relationship with adolescent attitudes towards early marriage (p=0.073). Access to information is an influential issue to adolescents’ knowledge about the risk of early marriage so that those with low education and living in rural areas can have indifferent knowledge from those with high education and living in urban areas.